Analysis the economic growth factors of strategic zone in Aceh Province, Indonesia (International Journal of Scientific Research and Management (IJSRM), 2017)
The purpose of this study was to analyse the economic growth factors strategic zone in Aceh Province, Indonesia of 2010-2016. The data used was data panel consisting of six zones namely the central, north, east, southeastern, south and west. The independent variables was development gaps, government budget, electrical energy, information technology, labor from magister/doctor. Dependent variable was economic growth. The method used was panel data regression. The result show that a model of fixed effect good enough explain economic growth. Factors that Influential very significant was information technology and electrical energy